2018
DOI: 10.1111/1365-2435.13067
|View full text |Cite
|
Sign up to set email alerts
|

Abiotic and biotic interactions in the diffusive boundary layer of kelp blades create a potential refuge from ocean acidification

Abstract: Seaweeds are able to modify the chemical environment at their surface, in a micro‐zone called the diffusive boundary layer (DBL), via their metabolic processes controlled by light intensity. Depending on the thickness of the DBL, sessile invertebrates such as calcifying bryozoans or tube‐forming polychaetes living on the surface of the blades can be affected by the chemical variations occurring in this microlayer. Especially in the context of ocean acidification (OA), these microhabitats might be considered as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 89 publications
(157 reference statements)
2
63
0
Order By: Relevance
“…Figs. 2A,C,E,3A,C,E) and the CA ext and AE transporter mechanisms are increasingly relied upon, in agreement with Noisette and Hurd (2018) who found that boundary layer thickness was protective under OA.…”
Section: Discussionsupporting
confidence: 81%
“…Figs. 2A,C,E,3A,C,E) and the CA ext and AE transporter mechanisms are increasingly relied upon, in agreement with Noisette and Hurd (2018) who found that boundary layer thickness was protective under OA.…”
Section: Discussionsupporting
confidence: 81%
“…This increase in pH at the thalli surface was primarily dependent on photosynthesis, as shown by no significant Δ pH between ambient and low pH treatments when PSII was inhibited with DCMU. A metabolically-driven increase in pH within the diffusive boundary layer (DBL) in the light has been observed in fleshy (Noisette and Hurd, 2018) and calcifying (Cornwall et al, 2015(Cornwall et al, , 2013De Beer and Larkum, 2001;Hofmann et al, 2018Hofmann et al, , 2016Hurd et al, 2011) macroalgae. Encrusting coralline algae (Sporolithon durum) raised pH in the light 0.88 pH units from 8.0 pH after 1 h under a flow rate of 1.5 cm s −1 (Hurd et al, 2011), similar to the flow in our experiments (~2-3 cm s −1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Trials were conducted within a recirculating flume tank (Hurd et al ; Cornwall et al ; Noisette and Hurd ) but was filled with a greater volume of water (55 L) than used previously (46 L). The flume was filled with filtered seawater to a depth of 200 mm and operated within a temperature‐controlled room at 15°C.…”
Section: Methodsmentioning
confidence: 99%